(3JaSjQ GdYR Hf YHO GdSdGes - (3YHO GdYRjR Hf YHO GdSdGe Hf CHj GdbGSe Hf GdMSf GdSdej GdOeTbj, YR GdOjf GdedbH HSdWGf GdYdeGA,J (B660 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ aGJMI GdcJGH s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI GdfGS s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B249s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B453s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdJaSjQ hYdhe GdbQBfs